CHALLENGES IN ASSESSING SPEAKING PROFICIENCY IN ONLINE LEARNING DURING COVID-19 PANDEMIC - Zumrotul Fauziah; Giati Anisah (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The purpose of this research is to describe the challenges faced by high school English teachers in teaching and evaluating during online learning during the Covid-19 pandemic.The method used in this research is descriptive qualitative research. The researcher used observation, an open-ended questionnaire, and an interview to collect the data. The result showed that the teachers face some challenges in teaching speaking and assessing speaking in online learning. First, limited or shorter duration of teaching causes less speaking practice in the process of teaching and learning. Second, limited access to the online platform, this condition happened since not all students have sufficient internet connections during online learning. Third, less learning motivation from the students. Fourth, limited speaking performance activities, such as dialogue, role play, and other performing activities, are difficult to do in online learning. Those problems forced teachers to be innovative in redesigning teaching activities and authentic assessments for students’ speaking proficiency.